2021
DOI: 10.2196/25893
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transparency, Trust, and Social Influence on Uncertainty Reduction in Times of Pandemics: Empirical Study on the Adoption of COVID-19 Tracing Apps

Abstract: Background Contact tracing apps are an essential component of an effective COVID-19 testing strategy to counteract the spread of the pandemic and thereby avoid overburdening the health care system. As the adoption rates in several regions are undesirable, governments must increase the acceptance of COVID-19 tracing apps in these times of uncertainty. Objective Building on the Uncertainty Reduction Theory (URT), this study aims to investigate how uncerta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 91 publications
(145 reference statements)
8
90
0
Order By: Relevance
“…The IDCTA should be voluntary and consent-based according to the WHO and ECDC ethical guidance on DCTAs, and this view is also prevalent in the academic literature [ 40 , 51 - 55 ]. For voluntary DCTAs, ensuring transparency and trustworthiness is important to maximize population penetration [ 52 , 53 , 71 - 79 ]. Transparency can be achieved by making the underlying DCTA algorithms open source [ 52 , 80 , 81 ], and this is established as best practice [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IDCTA should be voluntary and consent-based according to the WHO and ECDC ethical guidance on DCTAs, and this view is also prevalent in the academic literature [ 40 , 51 - 55 ]. For voluntary DCTAs, ensuring transparency and trustworthiness is important to maximize population penetration [ 52 , 53 , 71 - 79 ]. Transparency can be achieved by making the underlying DCTA algorithms open source [ 52 , 80 , 81 ], and this is established as best practice [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…This area should be a focus of future research. DCTAs need to detect contact events accurately to optimize uptake [ 79 , 105 , 144 , 145 ]. Ultra-wideband is a low energy means of enabling short-range high bandwidth communications that can transmit data with minimal noise interference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ample research has demonstrated that intentions do not necessarily translate to actual behavior [ 55 ]. Accordingly, two studies on CTAs reported a gap between the intention and the actual installation of the app [ 45 , 56 ]. Moreover, due to the clear prosocial framing in the experiment, social desirability bias might have been an important factor influencing its outcome.…”
Section: Introductionmentioning
confidence: 99%